Validated enzyme‐linked immunosorbent assay for determination of rosuvastatin in plasma at picogram level. Issue 5 (13th October 2011) - Darwish, Ibrahim A.; Al‐Obaid, Abdul‐Rahman M.; Al‐Malaq, Hamoud A.
Abstract : In this study, a highly sensitive enzyme‐linked immunosorbent assay (ELISA) has been developed and validated for the determination of rosuvastatin (ROS) in plasma samples at picogram level. The assay employed a polyclonal antibody that specifically recognizes ROS with high affinity, and ROS conjugate of bovine serum albumin (ROS–BSA) immobilized onto microplate wells as a solid phase. The assay involved a competitive binding reaction between ROS, in plasma sample, and the immobilized ROS‐BSA for the binding sites on a limited amount of the anti‐ROS antibody. The bound anti‐ROS antibody was quantified with horseradish peroxidase‐labelled second anti‐rabbit IgG antibody (HRP‐IgG) and 3, 3`, 5, 5`‐tetramethylbenzidine (TMB) as a substrate for the peroxidase enzyme. The concentration of ROS in the sample was quantified by its ability to inhibit the binding of the anti‐ROS antibody to the immobilized ROS‐BSA and subsequently the colour intensity in the assay wells. The assay limit of detection was 25 pg ml –1 and the effective working range at relative standard deviations (RSD) of ≤ 5% was 40–2000 pg ml –1 . Analytical recovery of ROS from spiked plasma was 96.2 – 104.8 ± 2.12 – 5.42%. The precision of the assay was satisfactory; RSD was 2.47 – 4.46 and 3.24 – 5.27% for the intra‐ and inter‐assay precision, respectively. The analytical procedure is convenient, and one can analyze 200 samples per working day, facilitating the processing of large‐number batch of samples. The proposed ELISA has a great value in routine analysis of ROS for its pharmacokinetic studies. Copyright © 2011 John Wiley & Sons, Ltd. Abstract : A sensitive ELISA has been developed and validated for determination of rosuvastatin in plasma samples at pictogram level based on a competitive binding immuno‐reaction.